Rational synthesis of Cu7S4/CoS2 hybrid nanorods arrays grown on Cu foam from metal-organic framework templates for high-performance supercapacitors - Zhou, Yan; Li, Yanli; Chen, Hongmei; Han, Lei (Journal of alloys and compounds, 2019)
Nanostructured copper sulfides with well-controlled morphologies, sizes, crystalline phases and compositions have been the subject of extensive research as the promising candidates in energy-related applications due to their excellent semiconducting properties and environmental compatibility. In this work, Cu7S4/CoS2 hybrid nanorods arrays on copper foam with different Co/Cu molar ratios (denoted as Cu-Co-S/CF-x, x = 0.12, 0.25 and 0.5) were firstly fabricated by a facile metal-organic framework templated synthetic strategy with three-step procedures of in situ interface growth, cation exchange and sulfurization. The optimized Cu-Co-S/CF-0.25 binder-free electrode displays the highest specific capacitance of 2132.7 mF cm−2 at a current density of 3 mA cm−2 (762.2 F g−1 at 1 A g−1) and outstanding cycling stability (92.3% capacitance retention over 10000 cycles). What's more, the assembled asymmetric supercapacitor (Cu-Co-S/CF-0.25//AC ASC) device based on Cu-Co-S/CF-0.25 as positive electrode and activated carbon (AC) as negative electrode offers a high energy density of 82.8 μWh cm−2 at the power density of 1.1 mW cm−2 (27.6 Wh kg−1 at 1125 W kg−1), which also demonstrates long-term cycling stability. These impressive results reveal that a rational and effective strategy has been explored to prepare binary transition metal sulfide nanorods arrays from metal-organic framework template for high-performance energy storage and conversion devices. Cu7S4/CoS2 hybrid nanorods arrays on copper foam were fabricated by a facile metal-organic framework templated synthetic strategy, which displayed high specific capacitance and excellent cycling stability as binder-free electrode for supercapacitor. [Display omitted] •Cu7S4/CoS2 hybrid nanorods arrays were fabricated by metal-organic framework templated synthetic strategy.•Optimized Cu-Co-S/CF-0.25 displays the high specific capacitance and the outstanding cycling stability.•Assembled asymmetric supercapacitor device offers high energy density and long-term cycling stability.•The enhanced electrochemical performances could be attributed to the synergistic effect of binary metal sulfides composite.